Mechanical thrombectomy and rescue therapy for intracranial large artery occlusion with underlying atherosclerosis. (4th December 2017) - Jia, BaiXue; Feng, Lei; Liebeskind, David S; Huo, Xiaochuan; Gao, Feng; Ma, Ning; Mo, Dapeng; Liao, Xiaoling; Wang, Chunjuan; Zhao, Xingquan; Pan, Yuesong; Li, Hao; et al.
Abstract : Objective: To investigate the safety and efficacy of mechanical thrombectomy plus rescue therapy for intracranial large artery occlusion (ILAO) with underlying intracranial atherosclerosis (ICAS). Methods: Patients enrolled in the intervention group of EAST (Endovascular Therapy for Acute ischemic Stroke Trial) were analyzed. For underlying ICAS identified during the stent retrieval procedure, rescue treatment was required for those with (1) a degree of arterial stenosis >70% or (2) any degree of arterial with blood flow impairment or (3) evidence of re-occlusion. Outcomes were compared between the ICAS group and the embolic group. Multivariate logistic regression was performed to determine independent predictors of functional independence at 90 days. Results: Among the 140 patients included in the analysis, underlying ICAS was identified in 47 (34%), and 30 patients (21.4%) were considered to be eligible to receive rescue treatment. Of the 30 patients, 27 (90%) actually received rescue therapy. Recanalization rate (95.7% vs 96.8%, P=0.757) and functional independence at 90 days (63.8% vs 51.6%, P=0.169) were comparable between the ICAS group and the embolic group. No significant difference in symptomatic hemorrhage (4.3% vs 4.3%, P=1.000) or death (12.8% vs 12.9%, P=0.982) was found between the two groups. National Institutes of Health Stroke Scale score at presentation (OR=0.865, 95% CI 0.795 to 0.941; P=0.001) and modified Thrombolysis in Cerebral Infarction after the procedure (OR=2.864, 95% CI 1.018 to 8.061; P=0.046) were independently associated with functional independence at 90 days. Conclusions: Mechanical thrombectomy is safe in patients with ILAO with underlying ICAS. By employing a standard rescue therapy, favorable outcomes could be achieved in such patients. Clinical trial registration: NCT02350283 (Post-results).